2017
DOI: 10.1111/scs.12402
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adolescents’ sense of coherence and health

Abstract: The aim of this systematic review was to describe the association between adolescent sense of coherence (SOC) and health and identify the future direction for research in this area. Systematic searches were conducted (2007-2014) in the PubMed, CINAHL, PsycINFO and Cochrane electronic databases and carried out manual searches in three scientific journals. A total of 827 original papers were found and 23 were selected. Based on the results, adolescents' sense of coherence (SOC) was related to health in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 45 publications
(146 reference statements)
7
64
0
6
Order By: Relevance
“…Over the years, an impressive amount of psychosocial research provided evidence that people with a strong SOC are less vulnerable to stressful situations. SOC was consistently found to be positively related to health in terms of physical and psychological well-being, self-esteem, self-efficacy, health behaviors, family relationships quality across life adversities, life development span, and cultures (see, for reviews, Flensborg-Madsen et al, 2005;Erikson and Lindström, 2006;Länsimies et al, 2017). SOC does not represent a specific style of coping, but rather helps in choosing the appropriate coping strategy in different kinds of stressful situations (Einav and Margalit, 2020), both acute stress situations (i.e., unexpected facts which overwhelm our resources) and chronic stress situations (i.e., stressors which characterize our life daily).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, an impressive amount of psychosocial research provided evidence that people with a strong SOC are less vulnerable to stressful situations. SOC was consistently found to be positively related to health in terms of physical and psychological well-being, self-esteem, self-efficacy, health behaviors, family relationships quality across life adversities, life development span, and cultures (see, for reviews, Flensborg-Madsen et al, 2005;Erikson and Lindström, 2006;Länsimies et al, 2017). SOC does not represent a specific style of coping, but rather helps in choosing the appropriate coping strategy in different kinds of stressful situations (Einav and Margalit, 2020), both acute stress situations (i.e., unexpected facts which overwhelm our resources) and chronic stress situations (i.e., stressors which characterize our life daily).…”
Section: Introductionmentioning
confidence: 99%
“…A strong SOC predicts reduced stress and decreased internalizing or/and externalizing problems. A systematic review showed that adolescents' sense of coherence was related to health in terms of the quality of life, health behavior, mental health and family relationships [34]. Accordingly, results of various studies showed that adolescents with higher SOC reported a healthier lifestyle, a better quality of life, and well-being [35] or less body dissatisfaction [36,37] and higher physical activity [38].…”
Section: Introductionmentioning
confidence: 99%
“…Although several longitudinal studies clearly support the strong association between SOC and perceived good health, especially the mental dimension, the relationship between SOC and physical health is more complex. Previous review papers suggest the influence of SOC on mental health is more robust and consistent than that on physical health [Eriksson and Lindström, 2006;Länsimies et al, 2017].…”
Section: Introductionmentioning
confidence: 99%